A DFT study on the adsorption of SO2 on Alx-C2N (x = 1, 2) monolayer. Issue 15 (12th October 2020) - Yang, Biao; Li, Zhiwei; Fan, Rujing; Ma, Jianyi
ABSTRACT: In this paper, the Al-doped C2 N monolayers (Al-C2 N and Al2 -C2 N) are proposed as a new type of gas adsorbent for air pollution. Based on first-principle calculations, the adsorption properties of Al-C2 N and Al2 -C2 N for SO2 molecules were studied. The adsorption energy, charge transfer and structural parameters were calculated to find the most stable gas-adsorbing materials Al-C2 N and Al2 -C2 N. In addition, the interaction mechanism of SO2 with Al-C2 N and Al2 -C2 N surfaces was studied using state density (DOS), projected state density (PDOS) and electron density distribution. The values of adsorption energy were calculated to be −2.115 eV for Al-C2 N and −1.793 eV for Al2 -C2 N. It was found that the SO2 molecule interacts with the surface of Al-C2 N and Al2 -C2 N through strong adsorption energy. Therefore, we conclude that the interaction between SO2 and these two monolayers (Al-C2 N and Al2 -C2 N) is chemisorption, and the Al-C2 N and Al2 -C2 N monolayer might be a promising gas adsorbent for SO2 gas pollution.